Understanding the Anxiety-Related Experiences of College Students in Synchronous Classes Using Video-conferencing Platforms - Pineda, Maica S.; Alindayu, Jr., Isidro D.; Silvestre, Angelo Aga D.; Credo, Chillet G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The pandemic caused by the spread of Coronavirus had brought sig-nificant changes to academic institutions. One notable change is the reliance to technology in conducting online synchronous class in the form of video-conferencing. The changes brought about by the pan-demic have been accompanied by a rise in different psychological issues such as anxiety. Given that most studies conducted in the Phil-ippines focus on the effects of COVID-19 on college students’ learning processes and mental health, further exploration is needed to better understand students’ experiences with video conferencing platforms in online synchronous classes. To achieve the purpose of the study, phenomenological approach and applied interpretative phenomeno-logical analysis were utilized. The findings revealed four main themes: on the use of technology, intrapersonal awareness of anxiety, interpersonal awareness of anxiety, and on coping with anxiety. These findings are valuable for academic institutions in developing policies to manage students’ anxiety related to videoconferencing. Academic institutions are encouraged to go beyond focusing solely on the academic outcomes of the students and revisit traditional frame-works and integrate mental health considerations. Development and validation of psychometric instruments to accurately measure video-conferencing-related anxiety is recommended. Conducting meta-analyses of existing research can help identify patterns and underly-ing factors influencing student anxiety in virtual learning environ-ments.